ESG risk and tax avoidance: Signaling insights from Indonesian public firms - Firmansyah, Amrie; Pratama, Helmi Putra; Valensa, Musyaffa Falma (Educoretax, 2025)
This study investigates the effect of Environmental, Social, and Governance (ESG) Risk on corporate tax avoidance among publicly listed firms in Indonesia. While prior research has widely examined the influence of ESG performance and disclosure on corporate fiscal behavior, limited attention has been paid to ESG Risk as a signal of sustainability governance weaknesses. Drawing on signaling theory, this study explores whether firms with higher ESG Risk scores, reflecting greater exposure to unmanaged ESG issues, are more likely to engage in tax avoidance practices. The analysis is based on a quantitative approach using cross-sectional data from 69 companies listed on the Indonesia Stock Exchange in 2022 that Sustainalytics has rated. Multiple linear regression analysis results reveal a significant negative relationship between ESG Risk and tax avoidance. This suggests that firms facing higher sustainability-related risks may attempt to restore their reputation or stakeholder trust by adopting more compliant fiscal strategies. The findings contribute to the literature by demonstrating how ESG Risk may function as a reputational signal that shapes corporate behavior beyond sustainability disclosures.